2022
DOI: 10.1016/j.cytogfr.2021.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Role of SARS-CoV-2 -induced cytokines and growth factors in coagulopathy and thromboembolism

Abstract: Severe COVID-19 patients frequently present thrombotic complications which commonly lead to multiorgan failure and increase the risk of death. Severe SARS-CoV-2 infection induces the cytokine storm and is often associated with coagulation dysfunction. D-dimer, a hallmark of venous thromboembolism (VTE), is observed at a higher level in the majority of hospitalized COVID-19 patients. The precise molecular mechanism of the disproportionate effect of SARS-CoV-2 infection on the coagulation system is largely undef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 186 publications
(205 reference statements)
1
20
0
1
Order By: Relevance
“…They regulate several pathophysiological conditions including tissue injury and repair through binding to specific receptors on the cell via paracrine and/or autocrine mechanisms [3] , [4] . SARS-CoV-2-induced cytokines and GFs mediate coagulation dysfunction and tissue injury, which contribute to the clinical severity of COVID-19 [5] , [6] . Changes in plasma cytokines and GFs level increases the risk of venous thromboembolism (VTE) [7] , [8] , characterized by elevated D-dimer and, a major cause of tissue injury in the severe COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…They regulate several pathophysiological conditions including tissue injury and repair through binding to specific receptors on the cell via paracrine and/or autocrine mechanisms [3] , [4] . SARS-CoV-2-induced cytokines and GFs mediate coagulation dysfunction and tissue injury, which contribute to the clinical severity of COVID-19 [5] , [6] . Changes in plasma cytokines and GFs level increases the risk of venous thromboembolism (VTE) [7] , [8] , characterized by elevated D-dimer and, a major cause of tissue injury in the severe COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of bacterial or viral infections, the immune system reacts through the release of both proinflammatory and anti-inflammatory cytokines essential to control and eliminate pathogens. However, following exposure to cells presenting SARS-CoV-2 antigen, T-cell reactivity has been shown to amplify cytokine release (cytokine storm) resulting in a positive feedback between immune cells and cytokines [92,93]. Indeed, in an infectious clinical setting, platelets express a number of immunoreceptors that enable them to act as specialized sentinels able to sense and, via receptors, recognize pathogens from all major classes of microorganisms invading the bloodstream [94].…”
Section: Platelets and Inflammationmentioning
confidence: 99%
“…In COVID-19, some of the dysregulated pro-inflammatory cytokines (IL-1β, IL-6, and IL-8) play a pathological role in promoting platelet activation and causing platelet dysfunction. For example, IL-1β could regulate platelet aggregation through its receptor IL-1R1 expressed on platelets [33]. In addition, other mechanisms related to the pathogenesis of COVID-19 include hypoxemia, increased inflammation, immune system activation, platelet apoptosis, and endothelial cell dysfunction, [34,35], which might further promote platelet activation, ultimately leading to thrombosis [36].…”
Section: Platelet Activationmentioning
confidence: 99%
“…Previous articles have demonstrated that SARS-CoV-2-induced pathological inflammation promotes the increased expression of P-selectin and the release of sCD40L, which together with thrombin promotes platelet activation. This, in turn, further increases thrombin, p-selectin, and sCD40L levels, creating a positive feedback loop that promotes platelet activation and thrombosis [33].…”
Section: Platelet Activationmentioning
confidence: 99%